Characterization of Organic Aerosol at a Rural Site in the North China Plain Region: Sources, Volatility and Organonitrates - Zhu, Qiao; Cao, Li-Ming; Tang, Meng-Xue; Huang, Xiao-Feng; Saikawa, Eri; He, Ling-Yan (Advances in atmospheric sciences, 2021)
The North China Plain (NCP) is a region that experiences serious aerosol pollution. A number of studies have focused on aerosol pollution in urban areas in the NCP region; however, research on characterizing aerosols in rural NCP areas is comparatively limited. In this study, we deployed a TD-HR-AMS (thermodenuder high-resolution aerosol mass spectrometer) system at a rural site in the NCP region in summer 2013 to characterize the chemical compositions and volatility of submicron aerosols (PM 1 ). The average PM 1 mass concentration was 51.2 ± 48.0 µg m −3 and organic aerosol (OA) contributed most (35.4%) to PM 1 . Positive matrix factorization (PMF) analysis of OA measurements identified four OA factors, including hydrocarbon-like OA (HOA, accounting for 18.4%), biomass burning OA (BBOA, 29.4%), less-oxidized oxygenated OA (LO-OOA, 30.8%) and more-oxidized oxygenated OA (MO-OOA, 21.4%). The volatility sequence of the OA factors was HOA > BBOA > LO-OOA > MO-OOA, consistent with their oxygen-to-carbon (O:C) ratios. Additionally, the mean concentration of organonitrates (ON) was 1.48–3.39 µg m −3 , contributing 8.1%–19% of OA based on cross validation of two estimation methods with the high-resolution time-of-flight aerosol mass spectrometer (HR-ToF-AMS) measurement. Correlation analysis shows that ON were more correlated with BBOA and black carbon emitted from biomass burning but poorly correlated with LO-OOA. Also, volatility analysis for ON further confirmed that particulate ON formation might be closely associated with primary emissions in rural NCP areas.